Assessment of Climate Services (CS) actors in selected regions in Vietnam from produces to end users - Barlis, Angelica; Imbach, Pablo; Ngan Vu; Duy Nhiem Nguyen; Thao Pham; Trung Nguyen Duc; Swaans, Cornelis P.M. (2021)
The report aims to assess the role, structure, and capacity-building needs of climate services (CS) actors in Vietnam. It identifies available climate information products and agro-advisories across different scales and examines the flow of this information from producers to users. The report evaluates CS actors' perceptions of climate information products based on legitimacy, credibility, and salience. Using a combination of qualitative and quantitative methods, the study explores the CS network, process, and information product, providing insights to improve climate risk management for agriculture in Vietnam. This assessment is part of a project aimed at developing climate risk management systems and insurance products for Southeast Asia (DeRISK SE Asia funded by IKI).